Countries in transition and GATT/WTO: Issues, expectations, prospects - Siegfried Schultz (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1995)
Applicant countries in transition wishing to revitalise or establish new ties with the GATT/WTO system will be able to achieve this neither in a rash nor uniform fashion. Undisputedly the necessary economic reforms in Central and Eastern Europe will take time. With respect to foreign trade, the economic reforms could be jeopardised without substantial improvement in the access to industrial country markets. However, the major remaining barriers to these markets are concentrated in sensitive areas, and protectionists' positions in favour of these barriers are generally stiff. To cushion detrimental effects of transformation and to prepare for ultimately joining the EU, particularly favourable conditions of market access have been extended in the framework of the Europe Agreements. This offer is open to a limited number of countries only. For the remaining majority of countries in transition there is some preferential treatment, the net effect of which is moderate. The alternative to regional schemes of preferences is the access to the world market as shaped by GATT/WTO provisions. Some of the applicants will have a long way to go before they qualify. For a realistic assessment of the chances of all of them, the WTO rules of accession should be clear, specified in advance, and the screening procedures transparent to avoid any impression of arbitrary decisions.
Keywords: 330; Handelsliberalisierung; Meistbegünstigung; Internationale Wirtschaftsbeziehungen; Osteuropa; Welt